Practicing history : new directions in historical writing after the linguistic turn - Spiegel, Gabrielle M. (Routledge, 2005)
"Gabrielle Spiegel presents an essential new collection of key articles that examine the current status of the debate over the 'linguistic turn', and attempt to rethink the practice of history in light of its implications. These are writings that operate within the framework of the linguistic turn, yet seek to move beyond its initial formulation and reception. The volume offers a synoptic overview of the last twenty-five years of theoretical analysis of historical writing, with a critical examination of the key concepts and positions that have been in debate. This collection delineates the emergence of a new 'practice theory' as a possible paradigm for future historical interpretation concerned with questions of agency, experience and the subject. Articles drawn from a mix of critical thinkers and practicing historians are drawn together along with clear and thorough editorial material. Complex ideas at the forefront of historical practice are revealed and made accessible to students, while for their teachers and other historians this new survey is an indispensable and timely read"--Provided by publisher.